The economic development of the British overseas empire - Knowles, L.C.A. (Lilian Charlotte Anne), 1870-1926.; Knowles, C. M. (Charles Matthew) (London: Routledge, 2005)
This book was first published by George Routledge & Sons Ltd. in 1924, 1930 and 1936. The first volume on the economic history of the British Empire is a comparative study, ranging from slavery to Factory Acts, from cold storage to ticks and mosquitoes, from rural cultures to plantation products, and from bush paths to railways. Volume I deals with economic and development issues relating to the Empire as a whole and also specifically with India, Malaya, Nigeria, Kenya and Uganda, while Volume II focuses more closely on Canada. Volume III covers the economic history of Australasia and South Africa.
v. 1. The Empire as a whole : the British Tropics / L.C.A. Knowles -- v. 2. Comparative view of Dominion problems : economic development of Canada -- v. 3. The union of South Africa.
Originally published: 1924-1936.
Includes bibliographical references and indexes.
lje 21/01/14
Loans
Keywords: Great Britain -- Colonies; Great Britain -- Colonies -- Economic conditions; Tropics; Canada -- Economic conditions; South Africa -- Economic conditions